EXTRATOS AQUOSOS DE PLANTAS MEDICINAIS NO CONTROLE DE NEMATOIDES DAS GALHAS. - Mateus, Milena Aparecida Ferrari (2012)
The objective of this study was to evaluate the efficiency of aqueous extracts of five species of medicinal plants, Verbena officinalis (L.), Erythrina mulungu (Mart. ex Benth.), Quassia amara (L.), Bidens pilosa (L.) e Plantago lanceolata (L.), in vitro, applied to soil or sprayed on tomato shoot for the control of Meloidogyne incognita and Meloidogyne javanica. For in vitro assays, we tested doses of 0, 10, 20, 30, 40 or 50 g L?¹ of different aqueous extracts. In acrylic-type ELISA, were placed separately into each well 100 üL of suspension containing 50 eggs of the nematode respective together with 100 üL of one of its treatment by keeping it in a growth chamber at 25ºC for 15 days . In the sixteenth day evaluated the number of second stage juveniles (J2) hatched per treatment. The aqueous extracts of V. officinalis, E. mulungu, Q. amara, B. pilosa e P. lanceolata, reduced the hatching of juveniles of M. incognita and M. javanica. The aqueous extracts of P. lanceolata showed the best results with up to 100% reduction in hatching rate for both nematodes. In vivo assays were conducted in a greenhouse and the variables evaluated were shoot height, fresh weight of shoot and root, number of galls, number of egg masses and number of eggs. According to the results obtained in in vivo tests, it was concluded that the aqueous extracts of V. officinalis and E. mulungu, when added to soil, showed higher efficiency control M. incognita, they affect the reproduction of this nematode. None of the extracts when added to soil, controlled M. javanica. None of the extracts as foliar spray was efficient in controlling nematodes. However, it should not be discarded the efficiency of these extracts in the control of nematodes, but, further studies should be conducted to determine other ways of extracting the active ingredients and different doses may have different results.